2011
DOI: 10.1597/08-244
|View full text |Cite
|
Sign up to set email alerts
|

Visual Face Perception of Adults with Unilateral Cleft Lip and Palate in Comparison to Controls—An Eye-Tracking Study

Abstract: When perceiving a face with a unilateral cleft lip and palate, the observer's gaze is distracted to the nose and mouth area. Moreover, participants with a unilateral cleft lip and/or palate themselves focused greater attention on those features that are anomalous on their own faces in comparison to participants without a cleft lip and palate. Specifically, this different scanpath is reflected in the cumulative duration of the eye movements as well as in the initial facial scan pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
2
49
0
4
Order By: Relevance
“…Meyer‐Marcotty et al . concluded that participants with UCLP and participants without CLP looked at faces of individuals with UCLP differently than they did unaffected faces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meyer‐Marcotty et al . concluded that participants with UCLP and participants without CLP looked at faces of individuals with UCLP differently than they did unaffected faces.…”
Section: Discussionmentioning
confidence: 99%
“…The eye‐tracking method has been used to evaluate how faces with severe Class III malocclusion, unilateral coronal synostosis and unilateral CLP are perceived visually. However, no data are available for faces with BCLP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It measures both involuntary and voluntary eye movements and fixations. This may be especially useful in examining an individual's external perception of visible asymmetries and anomalies [11][12][13][14][15][16]. Using this technique has provided us with objective measuring tool, which we have used to determine the extent to which facial anomalies in children with unilateral coronal synostosis are noticeable, as well as the region of the face that attracts the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca, DDY'li gözlemcilerin DDY'si olan ya da olmayan fotoğraflara, DDY'si olmayan gözlemcilere kıyasla burun bölgesine daha uzun süre ve göz bölgesine daha kısa süre baktığı bildirilmiştir. 28 DDY'li hastaların burun estetiğini daha çok önemsediğini gösteren bu çalışmadan yola çıka-rak; bu hastaların tedavi planlaması yapılır iken yüzün orta üçlüsüne daha fazla dikkat etmenin yararlı olabileceği sonucuna varılabilmektedir.…”
Section: Elde Edi̇len Veri̇leri̇n Değerlendi̇ri̇lme Bi̇çi̇mi̇unclassified